Does Job Satisfaction as a Predictor for Organizational Commitment? - Wustari L. Mangundjaya; Netty Merdiaty (Journal of Law and Humanities Review, 2025)
This article offers practical insights of the effects of job satisfaction and organizational commitment in the workplace, specifically in the context of the large banking industries in Indonesia.  The data, gathered from 3047 banking employees across the country, was rigorously analysed using simple regression analysis. The findings revealed that job satisfaction was a predictor of organizational commitment, with a score of 0.205 or an influence of 20.5%, for emerging organizational commitment, are highly significant. The findings revealed that job satisfaction is a predictor of organizational commitment, with a score of 0.205 or an influence of 20.5%, to emerging organizational commitment. Moreover, the results also indicated that job satisfaction was a more effective predictor of continuance commitment than the other two dimensions of organizational commitment. This finding was further supported by the employees’ motivation to join and stay in the organization. The practical implications of these findings are substantial as they can be harnessed to foster employee engagement, OCB, psychological well-being and and workplace well-being, thereby positively impacting the performance of both the employee and organization.